Maintain Customer Loyalty with Customer Relationship Management Approach: A Study of PT Fast Food Indonesia Tbk Surabaya Division - Imany Cinta Sevira; Harisatul Agustin; Mohamad Rijal Iskandar Zhulqurnain (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Purpose – This study seeks to examine the application of Customer Relationship Management (CRM) strategies by PT Fast Food Indonesia Tbk (KFC) in sustaining customer loyalty within a highly competitive food and beverage industry, particularly in light of KFC's leading market position accompanied by a declining revenue trend in 2024 relative to McDonald’s. Methodology – Employing a qualitative case study design, the research was conducted across seven KFC outlets in Surabaya from May to June 2025. Data collection involved semi-structured interviews and systematic observations with internal stakeholders (managers and cashiers) and external stakeholders (customers) directly involved in CRM implementation. Triangulation was utilized to enhance the validity and depth of data interpretation through the integration of diverse information sources. Findings – The investigation revealed the current practices of CRM implementation at PT Fast Food Indonesia Tbk, identifying both facilitating and constraining factors influencing its effectiveness in fostering customer loyalty amid intense industry competition. Practical implications – These findings provide critical insights for management at PT Fast Food Indonesia Tbk and comparable organizations to refine their CRM approaches, thereby improving customer engagement and competitive advantage. Social implications – Improved CRM strategies contribute to enhanced customer satisfaction and loyalty, ultimately benefiting the broader community by addressing consumer needs more effectively.